Wishing on a Christmas cowboy - Richardson, Sara (Romance fiction writer) (Richardson, Sara (Romance fiction writer). Star Valley novel, 2022)
"Pediatric nurse Kyra Fowler is finally going to realize her dream. She's got a job lined up at the most prestigious children's hospital in London. There's only one little snag--first she has to sell the Wyoming town she's just inherited from her estranged father. After a little fixing up, the place should easily attract a buyer. Hopefully she'll be celebrating the sale by New Year's. Ex-Navy SEAL Aiden Steele couldn't save his brother-in-law on the battlefield, but he can save his sister's ranch and give his nieces the life they deserve in the town they love. He's not about to let some outsider make a mint selling to a ruthless developer. Operation Save Star Valley is foolproof: show Kyra the sights, let the Christmas spirit work its magic, and bam! She'll decide not to sell and he can ensure his family is taken care of. Except as he tries to make Kyra fall in love with the town, Aiden starts falling for her" -- Back cover.